Skin-protective biological activities of bio-fermented Aframomum angustifolium extract by a consortium of microorganisms - Marion Albouy; Simon Aubailly; Olivier Jeanneton; Clarisse Marteau; Lauren Sobilo; Rachid Boulgana; Gerard Bru; Marine Bellanger; Emmanuelle Leblanc; Morgan Dos Santos; Karl Pays; Patrick Choisy; et al. (Frontiers Media S.A., 2023)
Background:Aframomum sp. is a genus of plants in the Zingiberaceae family. It includes several species, some of which are used in cosmetics for their various properties, making them useful in skincare products, particularly for anti-aging, moisturizing, and brightening the skin. However, to date, there is no experimental evidence on its natural extracts obtained or modified using microorganisms (bio-fermentation) as an anti-aging agent.Objective: The present study aimed to evaluate the antiaging effect of a Bio-fermented Aframomum angustifolium (BAA) extract on 3D bioprinted skin equivalent.Methods: The consortium of microorganisms contained Komagataeibacter, Gluconobacter, Acetobacter, Saccharomyces, Torulaspora, Brettanomyces, Hanseniaspora, Leuconostoc, Lactobacillus, Schizosaccharomyces. It was developed on a media containing water, sugar, and infused black tea leaves. The seeds of Aframomum angustifolium previously grounded were mixed with the culture medium, and the ferments in growth; this fermentation step lasted 10 days. Then, the medium was collected and filtered (0.22 µm) to obtain the BAA extract. To enhance our comprehension of the impact of BAA extract on skin aging, we developed skin equivalents using bio-printing methods with the presence or absence of keratinocyte stem cells (KSC). These skin equivalents were derived from keratinocytes obtained from both a middle-aged donor, with and without KSC. Moreover, we examined the effects of treating the KSC-depleted skin equivalents with Bio-fermented Aframomum angustifolium (BAA) extract for 5 days. Skin equivalents containing KSC-depleted keratinocytes exhibited histological characteristics typical of aged skin and were compared to skin equivalents derived from young donors.Results: The BAA extract contained specific organic acids such as lactic, gluconic, succinic acid and polyphenols. KSC-depleted skin equivalents that were treated with BAA extract exhibited higher specular reflection, indicating better hydration of the stratum corneum, higher mitotic activity in the epidermis basal layer, improved dermal-epidermal connectivity, and increased rigidity of the dermal-epidermal junction compared to non-treated KSC-depleted equivalents. BAA extract treatments also resulted in changes at the dermis level, with an increase in total collagen and a decrease in global laxity, suggesting that this extract could help maintain youthful-looking skin.Conclusion: In summary, our findings indicated that BAA extract treatments have pleiotropic beneficial effects on skin equivalents and that the bio-fermentation provides new biological activities to this plant.